The relationship between nurse stress and professional commitment in clinical nurses: A serial multiple mediation model through resilience and coping - Chia-En Hsieh; Li-Hua Huang; Ya-Lan Hsu; Tzu-Jung Wu; Hsiang-Chu Pai (PLOS One, 2026)
Objectives This study explored the association between work stress and professional commitment among clinical nurses, focusing on the serial multiple mediating effects of resilience and coping. Clinical nurses experience high levels of work stress that may negatively impact their professional commitment. However, the mechanisms underlying this relationship, particularly the mediating roles of resilience and coping, remain unclear. Materials and Methods This cross-sectional study was conducted at a single medical center and involved 345 clinical nurses recruited from internal medical and surgical wards, obstetric and pediatric wards, and emergency and critical care units. The valid response rate was 97.2%. All participants were recruited from inpatient units within the same medical center, ensuring a consistent clinical setting across all departments. Descriptive, univariate, and Pearson correlation analyses were performed, and mediation effects were tested using PROCESS Model 6. Results Nurse stress was significantly negatively associated with professional commitment (total association: c = −0.0808, p < 0.001). With resilience and coping as mediators, the direct effect remained significant (c′ = −0.0382, p = 0.0011). Conclusion Higher nurse stress was significantly associated with lower professional commitment. Resilience and coping were significantly associated with this relationship as serial mediating factors. Given the cross-sectional design, these findings should be interpreted as associations rather than causal effects. Strengthening resilience and adaptive coping may help support nurses’ professional commitment.